(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the level of work motivation (WM) among preventive healthcare staff at Go Vap District Health Center in 2024 and identify related factors. Method: A descriptive cross-sectional study design was used, surveying 163 healthcare staff using a self-administered questionnaire to assess WM based on the Mbindyo scale (2009). The questionnaire consists of 10 items covering three aspects: satisfaction, dedication, and commitment. Results: regarding overall WM, 59.5% had high motivation, while 40.5% had moderate motivation. The level of high WM was lowest for job satisfaction, with only 23.9%, followed by dedication at 70.6% and organizational commitment at 69.3%. Factors significantly associated with high WM included marital status (OR=2.61), management position (OR=2.63), professional category (nurses/medical assistants/midwives and other healthcare staff compared to doctors, OR=2.67 and 5.15, respectively), professional qualification (OR=0.43), satisfaction with colleagues (OR=4.06), and a safe working environment (OR=5.85). Conclusions: Many preventive healthcare staff exhibit low work motivation, highlighting the need for interventions related to income improvement, benefits, and the working environment. Such measures are essential in the current context to enhance motivation and job performance among preventive healthcare staff.